Do Fluctuations in U.S. Inflation Rates Reflect Infrequent Large Shocks or Frequent Small Shocks? - Bidarkota, Prasad V. (The Review of Economics and Statistics, 2003)
We investigate whether fluctuations in U.S. inflation rates are better described by infrequently occurring large shocks or by frequently occurring small shocks. We estimate a model that encompasses the two hypotheses within the framework of non-Gaussian state-space models. Our results indicate support for infrequently occurring large shocks, but this weakens somewhat once we allow for outliers and conditional heteroskedasticity. It appears that, for the purpose of forecasting monthly U.S. inflation rates, recognizing the distinction between frequent small shocks and infrequent large shocks does not matter much once outliers and conditional heteroskedasticity are allowed for.